Mindfulness training decreases the habituation response to persistent food stimulation - Torske, Alyssa; Schicker, Doris; Freiherr, Jessica; Koch, Kathrin (Scientific Reports, 2025)
Modern societies and their obesogenic environments expose individuals to persistent food stimulation. This frequent exposure can cause sensory systems to habituate or desensitize to food-related sensory stimulation. This can, in turn, lead to the reduction of pleasure associated with eating, which can elicit overeating behavior to attain the desired pleasurable effect. However, frequently engaging in overeating behavior can lead to excessive weight gain, which is associated with the development of metabolic and cardiovascular disease. Mindfulness training could serve as a tool to reduce the habituation response elicited by frequent food exposure while promoting mindful eating, emotion regulation, and reducing overeating behavior. To investigate this, the present study was registered as a clinical trial on the ISRCTN registry: trial ID ISRCTN12901054. In the study, meditation-naïve individuals with a tendency to stress-eat (N = 56) participated in either a 31-day, web-based, food-related mindfulness training or health training condition. Functional magnetic resonance imaging (fMRI) and behavioral data were acquired before and after the intervention. During the fMRI sessions, hungry and stressed participants were exposed to visual and olfactory high-calorie food stimuli. The results indicate that hunger and stress ratings increased in both groups during the fMRI sessions but that mindfulness training, in comparison to health training, may significantly reduce the habituation response to food stimuli. Our results demonstrate that the habituation response could be implicated through the increase of neural activity in brain regions involved in visual and olfactory processing as well as emotion regulation. This study, therefore, demonstrates that mindfulness training could improve the ability to attend to food stimuli, which may enhance the pleasurable experience of eating, thereby diminishing an individual’s tendency to engage in overeating behavior.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Eating behavior; Habituation response; Mindfulness; Neuroimaging; Sensory perception